Water-cooled radiofrequency neuroablation for sacroiliac joint dysfunctional pain - Binay Kumar Biswas; Samarjit Dey; Saumya Biswas; Varinder Kumar Mohan (Wolters Kluwer Medknow Publications, 2016)
Sacroiliac (SI) joint dysfunction is a common source of chronic low-back pain. Recent evidences from different parts of the world suggest that cooled radiofrequency (RF) neuroablation of sacral nerves supplying SI joints has superior pain alleviating properties than available existing treatment options for SI joint dysfunctional pain. A 35-year-old male had intractable bilateral SI joint pain (numeric rating scale [NRS] - 9/10) with poor treatment response to intra-articular steroid therapy. Bilateral water cooled = RF was applied for neuroablation of nerves supplying both SI joints. Postprocedure pain intensity was 5/10 and after 7 days it was 2/10. On 18th-month follow-up, he is pain free except for mild pain (NRS 2/10) on occasional extreme twisting of the back. This case attempts to highlight that sacral neuroablation based on cooled RF technique can be a long lasting remedial option for chronic SI joint pain unresponsive to conventional treatment.